Direct Commissive Speech Act in President Joe Biden’s Address to Congress - Odi Astaman; Akhyar Rido (Universitas Teknokrat Indonesia, 2023)
In a speech event, it is common for the speaker may be hiding various meanings from the listeners in addition to just stating what they are saying. As a result, there are breaks in communication and understanding for the listeners. This current study was aimed to identify the types of direct commissive act and the literal meanings and pragmatic effects in President Joe Biden’s Address to Congress. Focusing on the types of commissive speech act based on Searle's theory while the literal meaning as well as the pragmatic effects were based on Austin's theory. This study employed a qualitative methodology. The data were collected through perusal of documents. The findings showed that all the six types of direct commissive acts – promise, commit, guarantee, offer, bet, and threat – were used in President Joe Biden Address. The literal meanings and pragmatic effects showed that not all of President Biden's states were true. The findings of this study can be used by students who are going to conduct studies in this aspect, in particular, research in the pragmatic field focusing on the study of speech acts. This study suggest that stakeholders should use the findings of this study as a tool of assessment of public’s point of view to leaders’ promises in the context of social and political speech.Keywords: Commissive Act, Illocutionary Acts, Pragmatic Approach, Speech Event